Pengembangan Bahan Ajar Berbasis Kearifan Lokal Permainan Kanikir Di Desa Hitu Lama Kecamatan Leihitu Kabupaten Maluku Tengah - Limba, Anatasija; Suharlan, Lisa (INSTITUT AGAMA ISLAM NEGERI AMBON, 2020)
The implementation of cultural values or traditions of local people in learning is something that is important to be done by teachers today. The use of teaching materials based on Local Wisdom is expected to preserve the positive values of the nation's culture in learning and produce maximum learning outcomes. This study aims to develop a valid, practical, and effective local high school physics teaching model for high school physics teaching and its implications for island-based physics learning in Leihitu District, Central Maluku Regency using the Plomp model. The research activities were carried out through the stages of development, namely 1) the development of a model of teaching materials for high school physics based on local wisdom in Leihitu District, Central Maluku Regency, and 2) The validity of small-scale empirical validity (small groups) of the developed model. The results obtained are teaching materials in the form of LKPD Physics High School Momentum and Impulse concepts based on local wisdom “permainan kanikir”.